Analysing the effects of residential mobility behaviours on the composition of personal network in Switzerland. Issue 8 (19th April 2021) - Drevon, Guillaume; Viry, Gil; Kaufmann, Vincent; Widmer, Eric D.; Gauthier, Jacques‐Antoine; Ganjour, Olga
Abstract: Individual life courses are marked by residential mobility often associated with family and workplace changes and therefore likely to be related to the types of personal relationships people develop and maintain. Evidence about the relationship between residential mobility behaviours over the life course and personal network composition is however scarce. This study investigates this relationship among 747 individuals living in Switzerland using regression models and standard deviational ellipse for analysing all residential locations in Switzerland and their duration over the life course. Results show that people with low residential mobility have personal networks centred around the partner and vertical family ties (parents and children), confirming that strong intergenerational ties develop in close proximity. By contrast, longer distance residential moves at the regional level are associated with small personal networks centred around peers and horizontal ties (such as friends and siblings). The network composition of people with mobility experiences at the national level does not differ from the network composition of non‐movers when controlling for socio‐demographic characteristics. Likewise, networks including in‐laws and extended family members and large mixed networks including both family and friends were not associated with a particular residential mobility trajectory. The density of the Swiss transport system enabling people to stay connected to family and friends may partly explain the weak association between residential mobility behaviours and the composition of personal networks.